2017
DOI: 10.15324/kjcls.2017.49.4.495
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Endocrinologic Complications in Thalassemia Major

Abstract: Thalassemia major is a genetic disorder with a defective synthesis of either the alpha or the beta chain of hemoglobin A. Blood transfusion is crucial for the survival in these patients. Unfortunately, endocrine dysfunction is a very common complication in these patients and is principally due to excessive iron overload as a result of frequent blood transfusions. Although regular blood transfusion may increase life expectancy, disturbances in growth and pubertal development, abnormal gonadal functions, impaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Iron accumulation in the endocrine glands causes endocrine disorders causing hypogonadotropic, adrenal insufficiency, growth hormone (GH) deficiency, hypothyroidism, hypoparathyroidism, hypogonadism, and diabetes mellitus. [16][17][18][19] Growth disturbances in thalassemia major patients due to hormonal disorders are very complex. This growth disturbance occurs due to iron overload in the endocrine and gonadal glands, which causes hypogonadotropic hypogonadism, hypothyroidism, hypoparatiorids, diabetes mellitus, growth hormone deficiency, adrenal insufficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron accumulation in the endocrine glands causes endocrine disorders causing hypogonadotropic, adrenal insufficiency, growth hormone (GH) deficiency, hypothyroidism, hypoparathyroidism, hypogonadism, and diabetes mellitus. [16][17][18][19] Growth disturbances in thalassemia major patients due to hormonal disorders are very complex. This growth disturbance occurs due to iron overload in the endocrine and gonadal glands, which causes hypogonadotropic hypogonadism, hypothyroidism, hypoparatiorids, diabetes mellitus, growth hormone deficiency, adrenal insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…It will affect the speed of bone growth on the bone growth plate so that the child's stature is short. 17,18,23 Hypogonadotropic-hypogonadism happens due to damage to the hypothalamus and anterior pituitary caused by hemosiderosis. The gonadotropins produced by the anterior pituitary are very sensitive to oxidative damage caused by iron overload.…”
Section: Discussionmentioning
confidence: 99%
“…19 Common endocrine complications include growth disturbance, impaired thyroid function, impaired gonadal dysfunction and diabetes mellitus. 20 Iron deposition in the endocrine glands lead to low production of hormones especially growth hormone (GH) and gonadotropin (LH and FSH). 21 A study done among 35 thalassemia major patients in India showed 87.5% of girls presented with primary amenorrhea and low FSH and LH level while 89.47% of boys had low free testosterone.…”
Section: Endocrine Complicationsmentioning
confidence: 99%